Avaliação do crescimento inicial de oliveira "Arbequina" em diferentes manejos do solo e dosagens de fósforo - Paulus, Eloi (2011)
In the global context, Brazil ranks among the largest importers of olive products, not having a significant agricultural production to meet domestic market. The olive tree, a tree species considered to longevity also helps to conserve soil and water sources, important in environmental preservation of agricultural regions. With this the purpose of this study was to evaluate the growth of olive trees in different soil and triple superphosphate (SFT). The deployment of the olive grove was in August 2009 in Itaara Santa Maria RS and focuses on Typic Regolith soil. The following coordinates are: Latitude: S 29 º 37 '28.8''Longitude: N 53 º 47' 10.6''and an average altitude of 432 meters above mean sea level, in the transition region between the Plateau region and the Central Depression. The experiment was conducted in two areas. Area (A1) with the following soil tillage and fixed dosage of 225 g plant-1 and TSP 75 g plant-1 KCl for all plants: PSC - tillage only pit, PCC - conventional pit with more harrowing and PESC - tillage with mulch pit more harrowing. We evaluated the physical attributes of soil density, porosity, micro porosity, macro porosity, soil resistance to penetration. Growth was assessed by measuring the diameter and plant height. Area (A2) were applied per plant the following dosage of 42% triple superphosphate (TSP), respectively: 0 g T1, T2 75 g, 150 g T3, T4 225 g. We used fixed doses of 60% potassium chloride (KCl) in the amount of 75 g plant-1 for all treatments. Soil preparation was CFSP. The experimental design was completely randomized design with four replications for A1 and A2. The tillage was performed only in the range of the planting area. For the cultivation of olive recommends the use of forms of conservation management, such as planting only in the grave, to improve the physical and chemical characteristics of soil, especially the input of organic matter, which is most affected by tillage adopted in study area. The best effect of phosphorus on the growth in diameter and height was 75 g plant-1. However, one must be careful in extrapolating these results to different soil